PERFORMANCE OF THREE BROILER HYBRIDS FEEDING DIETARY WITH ANIMAL OR VEGETABLE PROTEIN RESOURCE : - Hazim AL-kassab (Mesopotamia Journal of Agriculture, 2012)
This study was conducted to determine the effect of hybrid type, source of diet protein , sex of bird and their interaction on carcass cuts and some characteristics of blood , Three hybrids bred from broiler (Cobb 500, Ross 308 and Hubbard Classic) by 300 chick is old unsexed one day of each hybrid, distributed randomly over 18 pen, 6 for each hybrid by 50 chicks for each replicate , Three replicates of each hybrid were fed diet containing animal and vegetable protein and 3 other replicates of the same hybrid fed the diet containing only vegetable protein until the age of 42 days , feed and water were available ad libitum, The results of statistical analysis have shown that the type of hybrid had significant effect (P ≤ 0,05) on some carcass cuts : the breast , wings and edible viscera (gizzard, heart and liver), as made hybrids Cobb 500 birds and Ross 308 significant superiority in the proportion of the breast compared with Hubb, hybrid , While the last Hybrid has achieved the highest final weight of the wings compared to the previous hybrids , There Was also a significantly effect of hybrid on the content of the carcasses (breast meats) of the moisture, extract ether, protein and ash % of the carcasses of the three male hybrids, while showed significant differences between the three female hybrids carcasses in the content of the protein only was the highest in carcasses of Cobb 500 hybrid , There are significant differences between the three hybrids in the concentration of total cholesterol and blood high-density lipoproteins - cholesterol, As for the effect of source of protein diet, there were a significant differences in the breast deterministic and some blood traits (total protein and albumin ) was in favor of excellence for birds fed on animal protein diet + plant together compared to those fed on vegetable protein diet only ,